THE STATE OF IMPLEMENTATION OF ORGANIZATIONAL AUTONOMY IN DOMESTIC INSTITUTIONS OF HIGHER - Vlasyuk, Oksana; Daragan, Tatiana (Educological discourse, 2021)
The article considers the need for the introduction of university autonomy, which will allow higher education institutions to be independent, self-sufficient. The state and tools of introduction of organizational autonomy in higher education institutions of Ukraine are analyzed. It is established that higher education institutions have the right to: independently develop the procedure for electing the head, within the legislation; determine the academic structure (scientific, educational-scientific, research, research and production institutes, faculties, departments); to create legal entities (to form innovative structures that will ensure the implementation of its statutory tasks and the implementation of innovative projects); adjust the number of external representatives in supervisory and academic boards (including the involvement of potential employers in their governing bodies and in the development and modernization of educational programs). The article identifies measures to expand organizational autonomy in domestic higher education institutions: the spread of decentralization of higher education; development of normative legal acts to increase the legal field of practical activity of universities; termination of participation of representatives of the Ministry of Education and Science of Ukraine in the election of the rector; weakening the procedure for participation in the governing bodies of representatives of civil society and commercial organizations. The state of implementation of organizational autonomy in Ukrainian higher education institutions is determined through the adaptation of the domestic legal framework on higher education to the indicators of its level assessment, defined by the Association of European Universities.